Consensus on Treatment and Follow-Up for Biochemical Recurrence in Castration-Sensitive Prostate Cancer: A Report From the First Global Prostate Cancer Consensus Conference for Developing Countries. (2021) - Monteiro, Fernando S. M.; Schutz, Fabio A.; Morbeck, Igor A. P.; Bastos, Diogo A.; de Padua, Fernando V.; Costa, Leonardo A. G. A.; Maia, Manuel C.; Rinck, Jose A.; Zequi, Stenio de Cassio; da Trindade, Karine M.; Alfer, Wladimir; Nahas, William C.; et al.
Abstract : PURPOSE: To present a summary of the treatment and follow-up recommendations for the biochemical recurrence in castration-sensitive prostate cancer (PCa) acquired through a questionnaire administered to 99 PCa experts from developing countries during the Prostate Cancer Consensus Conference for Developing Countries. METHODS: A total of 27 questions were identified as related to this topic from more than 300 questions. The clinician's responses were tallied and presented in a percentage format. Topics included the use of imaging for staging biochemical recurrence, treatment recommendations for three different clinical scenarios, the field of radiation recommended, and follow-up. Each question had 5-7 relevant response options, including "abstain" and/or "unqualified to answer, " and investigated not only recommendations but also if a limitation in resources would change the recommendation. RESULTS: For most questions, a clear majority (> 50%) of clinicians agreed on a recommended treatment for imaging, treatment scenarios, and follow-up, although only a few topics reached a consensus > 75%. Limited resources did affect several areas of treatment, although in many cases, they reinforced more stringent criteria for treatment such as prostate-specific antigen values > 0.2 ng/mL and STAMPEDE inclusion criteria as a basis for recommending treatment. CONCLUSION: A majority of clinicians working in developing countries with limited resources use similar cutoff points and selection criteria to manage patients treated for biochemically recurrent castration-sensitive PCa.